Multiagent System Technologies : 15th German Conference, MATES 2017, Leipzig, Germany, August 23-26, 2017, Proceedings /: 15th German Conference, MATES 2017, Leipzig, Germany, August 23-26, 2017, Proceedings. (2017) - Unknown
No abstract available